Evaluasi Geometri Jalan Tambang Menggunakan Teori AASHTO Untuk Peningkatan Produktivitas Alat Angkut Dalam Proses Pengupasan Overburden Di PIT Timur PT. Artamulia Tatapratama Desa Tanjung Belit, Kecamatan Jujuhan, Kabupaten Bungo Provinsi Jambi - Audia Multriwahyuni; Mulya Gusman; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2018)
Abstract.PT. Artamulia Tatapratama (PT. ATP) is a coal mining company with a surface mining system. As a result of not achieving the production target where one of the causes is the condition of the haul road, it is necessary to evaluate and improve the road. In this study, the geometry evaluation of the road will use the 1993 AASHTO.Based on the results of road geometry evaluation, the results obtained as follows: the actual straight road width is between 13-30 m while the theoretical road width should be 21.7 m. Actual road grades from Pit to disposal ranging from 2.47% to 11.30%. Cross slope from Pit to disposal is 440 mm / m. Superelevation figures of 26.88 meters curved is 0.04. So that the height difference between the inner and outer sides of the bend that must be made is 1.07 m. Actual productivity before road repair using a dump truck is Hitachi EH 1700 on average 98,309 BCM / Hour. Productivity has not reached the production target set by PT. Artamulia Tatapratama is 114 BCM / hour. As for productivity after road improvement 118,231 BCM / hour. The productivity has met the production target set by PT. Artamulia Tatapratama is 114 BCM / hour.  Keywords: Surface mining, Open Pit Mining, Haul Road, Overburden, Productivity